Transfer of amenamevir into breast milk in breastfeeding patients with recurrent herpes simplex: study protocol for a single-arm, open-label study - Koinuma, Sachi; Goto, Mikako; Saito, Jumpei; Murashima, Atsuko; Takeshita, Tomoyoshi (Frontiers in Pediatrics, 2025)
BackgroundRecurrent herpes simplex (RHS) is a disease caused by reactivation of the herpes simplex virus. Patients with RHS are treated with anti-herpes virus medication. Amenamevir is one such medication used for RHS in Japan and is administered as patient-initiated therapy (PIT); this involves initiation at the discretion of the patient, based on early symptoms. However, there are insufficient data on the transfer of amenamevir into breast milk among breastfeeding patients with RHS.ObjectivesThis study aims to assess the transfer of amenamevir into breast milk and evaluate the infant's risk of drug exposure.MethodsThis study is a single-arm, open-label, interventional multicenter study. Patients who experience RHS during breastfeeding will be recruited and treated with amenamevir. The concentration of amenamevir in breast milk will be determined by liquid chromatography-mass spectrometry. The primary outcome is relative infant dose (RID) calculated by Cave[AUC(0–24 h)]. The secondary outcome is RID calculated by Cmax and Cave[AUC(0–48 h)].DiscussionThis study will provide evidence of the transfer profile of amenamevir into breast milk during PIT. If the RID of amenamevir is less than 10%, such therapy is generally considered to be safe, and use of PIT with amenamevir may consequently lead to a new standard therapy for breastfeeding patients.